Cepolacanthus kimi, a new genus and species of copepod (Cyclopoida: Taeniacanthidae) parasitic on Bandfish Acanthocepola abbreviata (Valenciennes, 1835) (Actinopterygii: Cepolidae) caught off the Iraqi coast - Maran, Balu Alagar Venmathi; Moon, Seong Yong; Adday, Thamir Katea; Tang, Danny (Zootaxa, 2016)
A new genus and species, Cepolacanthus kimi, of the family Taeniacanthidae is established based on adult female specimens collected from the gills of Bandfish Acanthocepola abbreviata (Valenciennes, 1835) (Actinopterygii: Perciformes: Cepolidae) caught off the coast of Iraq. The new genus is characterised by the following combination of features: 1) the urosome is composed of five somites, with the last urosomite probably being a compound somite formed from the failure of the third and fourth abdominal somites to separate; 2) the seta on the maxillary basis is displaced proximally from the free spinulated element; 3) the terminal claw (endopod) of the maxilliped is long and attenuate; 4) the endopod of legs 2–4 is 2-segmented; and 5) the terminal exopodal segment of leg 4 bears a prominent distolateral protuberance. Cepolacanthus kimi gen. et sp. nov. is the first copepod reported from A. abbreviata and the second taeniacanthid species recorded from the Iraqi coast. A new replacement name, Suncheonacanthus nom. nov., is proposed for the preoccupied generic name, Triacanthus Kim & Moon, 2013.